2016
DOI: 10.20344/amp.6704
|View full text |Cite
|
Sign up to set email alerts
|

Tireoidite de Hashimoto e Doença Periodontal: Uma Revisão Narrativa

Abstract: RESUMOIntrodução: Atualmente há um crescente interesse no estudo das condições sistémicas com repercussões no periodonto. O objetivo deste artigo é determinar se existe uma relação entre a tireoidite de Hashimoto e a doença periodontal. Material e Métodos:Fundamentada na periodontologia baseada na evidência e na combinação das expressões: 'Hashimoto disease'; 'Hypothyroidism'; 'Periodontal diseases'; 'Systemic diseases'; optou-se pela pesquisa e avaliação de artigos presentes nas bases de dados Medline, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A narrative review on the relationship between periodontal disease and Hashimoto's disease identified the possibility of an association between these two conditions, based on common etiopathological mechanisms including the proliferation of T-helper 1 and T-helper 17 lymphocytes, impaired vascular endothelial function in the microcirculation of the periodontium, and influence on bone metabolism [ 14 ]. Another scoping review also found a positive relationship between hypothyroidism and periodontitis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A narrative review on the relationship between periodontal disease and Hashimoto's disease identified the possibility of an association between these two conditions, based on common etiopathological mechanisms including the proliferation of T-helper 1 and T-helper 17 lymphocytes, impaired vascular endothelial function in the microcirculation of the periodontium, and influence on bone metabolism [ 14 ]. Another scoping review also found a positive relationship between hypothyroidism and periodontitis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with periodontitis and hypothyroidism have a pathological change in metabolic processes, increased proteolytic activity of the blood and increased excretion of mineral components, especially calcium and phosphorus [14,15]. Analysis of the research results shows that thyroid dysfunction negatively affects the course of chronic inflammatory periodontal disease.…”
Section: Introductionmentioning
confidence: 99%